Effect of mechanical planting and weeding on yield, water-use efficiency and cost of production under modified system of rice intensification - MOHAPATRA, P C; DIN, M; PARIDA, B C; PATEL, S P; MISHRA, P (The Indian Journal of Agricultural Sciences, 2012)
Efficiency of planting and weeding equipments developed at Central Rice Research Institute, Cuttack was compared with traditional method of planting and weeding in relation to biomass yield, water-use efficiency (WUE) and net returns from SRI. The study showed that low plant density and high labour cost of SRI resulted in lower yield (3.77 against 4.52 tonnes/ha) and net returns (₹2 650 against ₹ 9 312/ha) compared to traditional method of cultivation. Mechanized planting and weeding of SRI enhanced its productivity to 4.24 tonnes/ha and profitability to ₹ 12 192/ ha. But it required that age of seedlings is increased from 8 to 16 days and density of hills is increased from 11 to 31/m2 with 4 (instead of single) plants/hill. Among mechanical planters, seeding by sprouted seeds on puddled soil by drum seeder was found to have significantly lower planting cost (₹ 515 against ₹ 1 332/ha) and lower total cost of production (₹ 16 355 against ₹17 767/ha). Average WUE (0.61 kg/m3) and grain yield (4.18 tonnes/ha) in weeded plots was double to un-weeded plots. Average cost of (single) weeding by weeders was ₹ 2 509 against ₹ 5 688/ha of manual weeding. Among the weeders, high efficiency in weed destruction and soil churning by star-cono weeder resulted in highest grain productivity and profitability in its favour.